ChemInform Abstract: Copper‐Catalyzed Cascade Reaction via Intramolecular Hydroamination Cyclization of Homopropargylic Amines and Intermolecular Povarov Reaction with Imines. Issue 43 (7th October 2016) - Wang, Hongkai; Wang, Chan; Huang, Kaimeng; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: A series of hexahydro‐1H‐pyrrolo[3, 2‐c]quinoline derivatives is synthesized in good to high yields by a one‐pot cascade reaction of homopropargylic amines with simple imines in the presence of Cu(OTf)2 .